Science’s ways to confront covid-19 fake news - Raquel, Cheila Pires; Ribeiro, Kelen Gomes; Alencar, Nadyelle Elias Santos; Souza, Daiana Flávia Oliveira de; Barreto, Ivana Cristina de Holanda Cunha; Andrade, Luiz Odorico Monteiro de (Saúde e Sociedade, 2023)
Parallel to the covid-19 pandemic, the World Health Organization warns of an infodemic of fake news related to the disease. This integrative review investigates the dimension of this phenomenon and the ways identified by science to confront it. Bibliographic search was conducted on the Scopus/Elsevier and Medline/PubMed databases, retrieving 23 articles. Literature analysis identified that fake news provide false social support and mobilize feelings which make them more acceptable than the truth. Hence, social media and the internet emerge as platforms for spreading false information. Research suggests that government and media institutions can use communication channels, as well as monitoring and infosurveillance technologies, as allies to alert, clarify and remove misleading content. Investments in scientific and digital literacy actions, so that people may assess the quality of the information received is needed. Finally, the study proposes the adoption of creative strategies to awaken reasoning skills, combined with scientific information translated into accessible language, preferably approved by health and institutional authorities.